Rivulus berovidesi, a new killifish species (Teleostei: Rivulidae) from western Cuba - Silva, Rodet Rodriguez (Zootaxa, 2015)
Rivulus berovidesi, a new killifish species, is described from a small stream in Sierra de Cajalbana, northwestern Cuba. It is readily distinguished from Rivulus cylindraceus Poey by the combination of an exclusive color pattern and meristic characters such as a d-type frontal scalation pattern (versus e-type pattern in Rivulus cylindraceus). The current diagnosis of Rivulus berovidesi based on chromatic, morphological and meristic characters is consistent with a recent molecular analysis of this genus in Cuba.